Deformation Quantization and Representations of the Real Rotation Group - Nable, Job (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 1 (2001), 2007)
Excerpt In this paper we present concrete computations of representations of the real rotation group SO(3,R) arising from deformation quantization of its coadjoint orbit Ωξ = S^2.